Evaluation of the effects of different diets on microbiome diversity and fatty acid composition of rumen liquor in dairy goat. (8th January 2018) - Cremonesi, P.; Conte, G.; Severgnini, M.; Turri, F.; Monni, A.; Capra, E.; Rapetti, L.; Colombini, S.; Chessa, S.; Battelli, G.; Alves, S. P.; Mele, M.; et al.
Abstract : Fat supplementation plays an important role in defining milk fatty acids (FA) composition of ruminant products. The use of sources rich in linoleic and α -linolenic acid favors the accumulation of conjugated linoleic acids isomers, increasing the healthy properties of milk. Ruminal microbiota plays a pivotal role in defining milk FA composition, and its profile is affected by diet composition. The aim of this study was to investigate the responses of rumen FA production and microbial structure to hemp or linseed supplementation in diets of dairy goats. Ruminal microbiota composition was determined by 16S amplicon sequencing, whereas FA composition was obtained by gas-chromatography technique. In all, 18 pluriparous Alpine goats fed the same pre-treatment diet for 40±7 days were, then, arranged to three dietary treatments consisting of control, linseed and hemp seeds supplemented diets. Independently from sampling time and diets, bacterial community of ruminal fluid was dominated by Bacteroidetes (about 61.2%) and Firmicutes (24.2%) with a high abundance of Prevotellaceae (41.0%) and Veillonellaceae (9.4%) and a low presence of Ruminococcaceae (5.0%) and Lachnospiraceae (4.3%). Linseed supplementation affected ruminal bacteria population, with a significant reduction of biodiversity; in particular, relative abundance of Prevotella was reduced (−12.0%), whereas that of Succinivibrio and Fibrobacter was increased (+50.0% and +75.0%, respectively). No statistically significant differences were found among the average relative abundance of archaeal genera between each dietary group. Moreover, the addition of linseed and hemp seed induced significant changes in FA concentration in the rumen, as a consequence of shift from C18 : 2n-6 to C18 : 3n-3 biohydrogenation pathway. Furthermore, dimethylacetal composition was affected by fat supplementation, as consequence of ruminal bacteria population modification. Finally, the association study between the rumen FA profile and the bacterial microbiome revealed that Fibrobacteriaceae is the bacterial family showing the highest and significant correlation with FA involved in the biohydrogenation pathway of C18 : 3n-3.